The Impact of Different Tannin to Anthocyanin Ratios and of Oxygen on the Phenolic Polymerisation Over Time in a Wine-like Solution - G. Garrido-Bañuelos, G.; Buica, A.; Sharp, E.; de Villiers, A.; du Toit, W. J. (South African Journal of Enology and Viticulture, 2019)
Colour and phenolic stability during ageing are influenced by the levels of distinct classes of phenolics in young red wines. The ratios between different classes of phenolic compounds also determine the colour and phenolic development of red wines. The present study evaluated the impact of forced oxidation on different anthocyanin/tannin (A/T) extracts and its consequent effect on the colour and phenolic evolution over time. The results showed that higher contents of seed tannins could enhance phenolic polymer formation, especially in the presence of oxygen. The addition of oxygen seemed to favour certain polymerisation reactions between tannins, leading to higher concentrations of monomeric anthocyanins in solution. A slower oxygen consumption was also observed as the phenolic composition of the wine-like extract evolved over time.